Learn to containerize algorithms deploy to AWS with App Runner (Pragmatic AI Solutions, 2022)
Learn to build greedy algorithms, then convert them to microservices and finally containerized them and deploy to AWS with App Runner. 00:00 Intro 00:38 Github Code Repo of Traveling Salesman Problem 02:00 Overview of Cities in Problem 04:50 Launching Github Codespaces to work on problem 06:30 Cleaning up the code and fixing Makefile and Lint 09:30 Running simulations and minimizing the cost 14:00 Pinning version numbers in requirements.txt 16:00 Setup Github Actions 19:00 Fixing Python Black error 21:32 Create Github Actions Status Badge 25:00 Creating FastAPI Microservice 28:00 Building Greedy Coin Change Microservice 36:00 Deploying Python FastAPI Microservice to AWS with App Runner 46:00 Theory of logic to containerization 51:00 Building Containerized C# Service in AWS Cloud9 and App Runner 01:03:44 Testing via Curl in AWS CloudShell 01:06:00 Building Containerized FastAPI Service in AWS Cloud9 and App Runner 01:11:03 Pushing to Amazon ECR 01:14:00 Testing via FastAPI App Runner API with Swagger UI.